Is serum fibroblast growth factor 21 associated with the severity or presence of coronary artery disease? - Nar Gokay; Cetin Sanlialp Sara; Nar Rukiye; Kilic Oguz; Furkan Ozen Mehmet; Gunver Guven; Ilyas Sevgican Cihan (Journal of Medical Biochemistry, 2022)
Background: Recent studies have shown that increased circulating concentrations of fibroblast growth factor 21 (FGF21) are associated with obesity, metabolic disorder, and atherosclerosis. However the relationship between FGF21 and coronary artery disease (CAD) is controversial This study was planned to investigate the role of FGF21 in CAD development and CAD severity. Methods: Seventy-eight patients with stable angina pectoris (SAP) (lesion positive) and 40 control patients (lesion negative) with similar cardiovascular risk factors were included in the study. Serum FGF21 levels were measured by ELISA method. CAD severity was evaluated by using SYNTAX and GENSINI risk scores. Results: FGF21 concentrations were found significantly higher in the SAP group than in the control group. [101.18 ± 141.62 vs. 47.93 ± 58.74 pg/mL; p = 0.03], no correlation was found between the SYNTAX (r = 0.146 and p = 0.134) and GENSINI (r = 0.211 and p = 0.084) scores with serum FGF21 levels. There was a negative relationship between serum FGF21 and serum HDL-C levels in correlation analysis (r = - 0.272; p = 0.026). Conclusions: The serum FGF21 levels are different between SAP and control patients. FGF21 is a marker for CAD diagnosis, but not for the evaluation of CAD severity.